The Role Of Youth Organizations In Increasing Children's Reading Interest: A Case Study Of Oemah Dolan Organizations In Kedongdong Village, Susukan District, Cirebon Regencyil - Alifatuz Zahro (Balitbangda Provinsi Jambi, 2021)
The impact of the modernization era on elementary and Kindergaten children can be seen from the intensity of children playing with gadgets, and the low level of literacy in children. This is the background for the presence of the Oemah Dolan organization. This study aims to identify and describe Oemah Dolan's programs and the role of Oemah Dolan in increasing reading interest in children in Kedongdong Village. This study uses a descriptive-qualitative approach with the analysis technique of Miles and Huberman. The results of this study indicate that Oemah Dolan has several programs, namely: book stalls, reading, fun learning, and creativity week.